Effect Of Galactose And Fructose On The Expression Of Isocitrate Lyase (ICL1) Enzyme In Candida Albicans - Ting, Seng Yeat (2016)
The virulence of C. albicans is dependent upon fitness attributes as well as virulence factors. These attributes include robust stress responses and metabolic flexibility. C. albicans can occupy a variety niches in human, many of which contain a rannge of different carbon sources. The assimilation of these carbon sources is important for growth and essential for establishment of infections by C. albicans. This thesis examines the impact of galactose or fructose upon the assimilation of secondary carbon sources such as lactate by C. albicans Isocitrate lyase gene (CalCLI) is repressed upon addition of 2% galactose or fructose to lactate-grown cells.